INNOVATIVE TECHNOLOGIES OF PREPARING STUDENTS FOR SOCIAL LIFE AND THEIR IMPROVEMENT (Scientific journal of the Fergana State University, 2023)
This article discusses innovative technologies for preparing students for public life based on the pedagogy of cooperation and their improvement, as well as the priority of spirituality, national aesthetics and physical education in the process of forming national morality.